Ob'ektivnye predposylki sovershenstvovaniya dvigatel'nykh deistvii trenera na uroke fekhtovaniya - Bychkov, Yu. M. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper was to discuss the problem of coach's professional mastery in connection with the peculiarities of his motor actions of special character. The prac tical recommendations to coaches about their motor actions in different situations of fencing individual training are offered. The effectiveness of the coach's motor ctions is determined by his adequate reaction to the athlete's actions and the coach's efforts to prevent the technical inaccurasies, when serving the pupil's actions by weapon.